Diversity of Cultivable Bacteria in A Saline Desert of Little Rann of Kutch, India: A Phylogenetic Perspective - Bhatt, Hitarth B.; Singh, Satya P. (Frontiers in Marine Science, 2022)
Deserts in general and Indian deserts in particular are less attended for microbial diversity. The Little Rann of Kutch (LRK), a coastal saline desert, is characterized by a unique combination of both dry and wet features. This study represents the first report on the extensive isolation, spatial distribution, 16S rRNA gene-based phylogeny and identification of novel taxa. A total of 87 isolates were obtained from three different study sites of LRK. Based on the full 16S rRNA gene sequences, the isolates were grouped into 44 different phylotypes of 4 phyla; Firmicutes, Proteobacteria, Actinobacteria and Euryarchaeota represented by 19 different genera. Halomonas, Gracilibacillus, Thalassobacillus, Piscibacillus, Salimicrobium, Alkalibacillus, Bhargavaea, Proteus, Marinobacter, Pseudomonas, Kocuria, Corynebacterium, Planococcus, Micrococcus and Natronococcus identified in this study were never reported earlier from this habitat. Majority of the isolates displayed broad salt and pH tolerance. Venasar and Jogad sites closely resembled for bacterial diversity as compared to Surajbari. While Bacillus, Virgibacillus, Gracillibacillus and Bhargavaea were common genera in all sites, six putative novel taxa of different phylogenetic groups identified. Available nitrogen, pH, Organic carbon, TDS and EC were the main environmental variables affecting the microbial diversity. Analysis of the geographical distribution revealed that majority of the phylotypes had cosmopolitan distribution followed by the saline and marine distribution, while ∼13% affiliated with only LRK. The phylotypes associated with marine distribution decreased with increasing distance from the Gulf of Kutch, suggesting their endemic nature of the marine environments. The study established the taxonomic novelty and prospects for the discovery of unique products and metabolites.